2018
DOI: 10.1038/s41598-018-32910-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased TIMP-3 expression alters the cellular secretome through dual inhibition of the metalloprotease ADAM10 and ligand-binding of the LRP-1 receptor

Abstract: The tissue inhibitor of metalloproteinases-3 (TIMP-3) is a major regulator of extracellular matrix turnover and protein shedding by inhibiting different classes of metalloproteinases, including disintegrin metalloproteinases (ADAMs). Tissue bioavailability of TIMP-3 is regulated by the endocytic receptor low-density-lipoprotein receptor-related protein-1 (LRP-1). TIMP-3 plays protective roles in disease. Thus, different approaches have been developed aiming to increase TIMP-3 bioavailability, yet overall effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 65 publications
(82 reference statements)
0
33
0
Order By: Relevance
“…In addition, the catalytic activity of several metalloproteinases can be post-translationally activated by proteolytic removal of their inhibitory pro-domain 4,6 . Moreover, a major mechanism that regulates the extracellular levels of several MMPs (including MMP-2 8 , MMP-9 9 and MMP-13 10,11 ) ADAMTSs (including ADAMTS-1 12 , ADAMTS-4 13 and ADAMTS-5 14 ) and TIMPs (including TIMP-1 15 , TIMP-2 8 , TIMP-3 16,17 ) is endocytosis and subsequent lysosomal degradation via the scavenger receptor low-density lipoprotein receptor-related protein 1 (LRP-1) 8,9 . LRP-1 is considered to be a master regulator of ECM turnover, since the affinity of individual metalloproteinases and TIMPs for LRP-1 determines their extracellular half-life and so controls the balance between ECM degradation and deposition.…”
mentioning
confidence: 99%
“…In addition, the catalytic activity of several metalloproteinases can be post-translationally activated by proteolytic removal of their inhibitory pro-domain 4,6 . Moreover, a major mechanism that regulates the extracellular levels of several MMPs (including MMP-2 8 , MMP-9 9 and MMP-13 10,11 ) ADAMTSs (including ADAMTS-1 12 , ADAMTS-4 13 and ADAMTS-5 14 ) and TIMPs (including TIMP-1 15 , TIMP-2 8 , TIMP-3 16,17 ) is endocytosis and subsequent lysosomal degradation via the scavenger receptor low-density lipoprotein receptor-related protein 1 (LRP-1) 8,9 . LRP-1 is considered to be a master regulator of ECM turnover, since the affinity of individual metalloproteinases and TIMPs for LRP-1 determines their extracellular half-life and so controls the balance between ECM degradation and deposition.…”
mentioning
confidence: 99%
“…Another recent study using HEK293 cells that overexpress TIMP-3 show evidence of reduced ADAM10-specific substrates after secretome analysis by mass spectrometry label free quantification. This study showed that with TIMP-3 overexpression, several ligands for the low-densitylipoprotein receptor-related protein-1 (LRP-1) are upregulated, such as macrophage inhibitor factor (MIF) (88). As TIMP-3 also binds to LRP-1, overexpression of TIMP-3 outcompetes other ligands of LRP-1 and thus the cell compensates by increasing expression (88).…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%
“…This study showed that with TIMP-3 overexpression, several ligands for the low-densitylipoprotein receptor-related protein-1 (LRP-1) are upregulated, such as macrophage inhibitor factor (MIF) (88). As TIMP-3 also binds to LRP-1, overexpression of TIMP-3 outcompetes other ligands of LRP-1 and thus the cell compensates by increasing expression (88). The authors of this study warn that the use of TIMP-3 interventions as an ADAM10 regulator could yield these alterations to the secretome and results might be unanticipated.…”
Section: Oral Squamous Cell Carcinomamentioning
confidence: 99%
“…Particularly, fibroblasts of the nodular sclerosing subtype of cHL express high amounts of the tissue inhibitor of metalloproteinases 3 (TIMP3) (18). Although TIMP3 principally inhibits ADAM10 and ADAM17, it predominantly blocks ADAM10 in vivo (19). Thus, sheddase inhibition in the tumor microenvironment of certain cases of cHL might influence the amount of EVassociated CD30.…”
Section: Quantification Of Released Cd30 Formsmentioning
confidence: 99%